United Nations Commission on International Trade Law (UNCITRAL) Yearbook 2014 - United Nations (United Nations, 2019)
The UNCITRAL Yearbook is a compilation of all substantive documents related to the work of the Commission and its Working Groups. It also reproduces the annual Report of the Commission which is published as Supplement No. 17 of the “Official Records of the General Assembly”. The Yearbook is published in English, French, Russian and Spanish. UNCITRAL is the core legal body of the United Nations system in the field of international trade law. It specializes in the modernization and harmonization of rules on international business.